A cross sectional study on social media usage and health status among under graduate medical students studying in Government medical college Telangana - Munnaji V., Mavatkar (International Journal Of Community Medicine And Public Health, 2019)
Background: Today utilization of social media has become an integral part of young population. India is on the hike for development and internet has been the center point of that. Thus finding the current status is necessary. Methods: The design of the study was cross sectional observational study. Sample size of the study was 140 students from second year MBBS. The place of study was at Government Medical College, Telangana. The subject of the study was second year MBBS students. The study period was from November 2018 to January 2019. Study tool was standard social media addiction scale and a pre-tested semi structured questionnaire. Results: Total number of participants was 138. Amongst the social media users out of 136 about 88 (63.76%) students were found to be mild social media addict and about 50 (36.23%) students were found to be moderately social media addict. Most common physical symptom observed in social media users overall was disturbance in sleep, i.e., 13.2%. Conclusions: In today’s world were internet has become the basic need for growth of science and technology, it has also encroached on to the routine daily activity thus inhibiting the performance of the student by affecting him physically and psychologically.